The photography as technique and object of study in qualitative research - Sadraque Oliveira Rios; Jean Mario Araujo Costa; Vera Lucia Peixoto Santos Mendes (Discursos Fotográficos, 2016)
This paper aims to discuss photography in qualitative research on literature review. Photograph is located in the context of technological developments in the nineteenth century, with its attributes as object and technical research, the advantages and limitations of its use and critical interpretation guidelines. In conclusion, we present the analysis of two scientific papers that make exemplary use of photography in qualitative research.